"My meemaw is a Cool Ass Person": Family Members as Role Models of Resilience for Sexual and Gender Diverse People of Color. Issue 2 (2nd March 2020) - Stone, Amy L.; Nimmons, Elizabeth A.; Salcido, Robert; Schnarrs, Phillip
Abstract: The families of people of Color and indigenous people (POCI) are often analyzed as hostile institutions for sexual and gender diverse (SGD) adults. Using 58 interviews with SGD POCI from the Strengthening Colors of Pride 2018 Interview Study, we argue that Black and Latinx SGD adults gain resilience from family role models, mostly resilient mothers and othermothers. These resilient family members model three things: 1) how to overcome adversity and trauma, 2) being providers, and 3) emotional strength. This resilient modeling facilitates the adult resilience of SGD POCI who are navigating the complexity of intersections of race, sexuality, gender, poverty, and childhood trauma.